A new species of coralsnake of the genus Calliophis (Squamata: Elapidae) from the Central Province of Sri Lanka - Smith, Eric N.; Manamendra-Arachchi, Kelum; Somaweera, Ruchira (Zootaxa, 2008)
We describe a new species of coralsnake, Calliophis haematoetron, from central Sri Lanka. This is the second species of coralsnake known from the island country, after Calliophis melanurus. It differs from C. melanurus in coloration, possessing a relatively unpigmented head (vs. capped with black from rostrum to nuchal collar), no light spots posterolateral to the parietal plates (vs. one at each side), a banded body dorsum (vs. unicolored), a bright red body venter (vs. orange or yellow through most of the length), and red pigment lateral to the blue under-tail color (vs. no red on tail). It also differs from C. melanurus in aspects of lepidosis, in having a frontal that is shorter or equal in size (vs. longer) than the interparietal suture and a first sublabial that does not touch the second pair of chin-shields (vs. first sublabial broadly touching second pair of chin-shields). The new species is easily distinguished from all other Calliophis species in nearby India and Southeast Asia by characters of external morphology and coloration.